Bureau Of Mines Mineral Investigations In The Juneau Mining District, Alaska, 1984-1988 - Volume 2.- Detailed Mine, Prospect, And Mineral Occurrence Descriptions - Section E - Coast Range Subarea ? Introduction - Location, Access, And Land Status - Albert H. Clough (The National Institute for Occupational Safety and Health (NIOSH), 2012)
The Coast Range subarea of the Juneau Mining District (JMD) extends from the Canadian border north of the community of Skagway, southerly to Tracy Arm. It is bounded by the international boundary on the north and eastern edges. The Ferebee Glacier and Lynn Canal mark the western boundary, extending south to the Berners Bay region. From Berners Bay south, the western boundary is the eastern boundary of the Juneau Gold Belt (fig. E-l). The city of Skagway (fig. E-2) is the only developed community within the confines of the subarea. Skagway was originally established as a port for the Klondike gold rush of 1898. Recently, Skagway has gained prominence as a port for shipping goods into and mineral products out of Yukon Territory (fig. E-3). Skagway has also developed a thriving tourist industry based on its Alaskan traditions. The community of Skagway maintains a paved airstrip which is suitable for use by small multi-engine aircraft. Several regional air carriers serve Skag-way with frequent scheduled flights, especially during the summer months. Helicopter charter services are available from Skagway during the summer months.